Bioenergetics Energy Conservation and Conversion - Schäfer, Günter; Penefsky, Harvey (Results and Problems in Cell Differentiation,, 2008)
The present book addresses fundamental questions of biological energy transformation and conservation, with a focus on those processes which can now be understood on a structural basis. Current knowledge of selected examples of the biological energy conservation machinery such as cellular oxygen respiration, light-driven energy converters, and fermentation is reviewed. The machinery is highly variable, particularly that within microorganisms, but all of these devices universally rely on one unique underlying physico-chemical principle. The book is a rich source for specialists interested in recent developments in bioenergetics research and novices in the field alike.